Parking Braking System Design for AC Drive Electric Locomotive - LIU Dexue; FANG Changzheng; AI Zhengwu; LIU Yuxiang (机车电传动)
Taking parking braking system for HXD1D electric locomotive as an example, the parking braking system control circuit theory, relationship between parking braking and control system, JPXZ-2 disk braking device and parking braking calculation were described. Lastly, operation and characteristic of parking braking system was explained.